PENGARUH KECERDASAN EMOSIONAL, KOMITMEN ORGANISASIONAL, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA KARYAWAN PT. BANK MUAMALAT CABANG MALANG - Andi Widodo; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen)
Abstract The purpose of this study is (1) to determine the effect of emotional intelligence, organizational commitnent, organizational citizenship behavior on employee performance. (2) to determine description the effect of emotional intelligence, organizational commitment, organizational citizenship behvior on employee performance. (3) to determine effect of emotional intelligence on employee performance. (4) to determine effect of organizational commitment on employee performance. (5) to determine effect of organizational citizenship behavior on employee performance. the population in this study on PT.Bank Muamalat branch Malang sampling technique using filsafat positivisme to obtain a sample.data collection trough questionnarire distribution. Data analysis in this research using SPSS version 16.0. data analysis methods used in this study include normality test, multiple linear regression test, classic assumption test and hypothesis test.            The result of this study indicate that the effect of emotional intelligence, organizational commitnent, organizational citizenship behavior has a  positive simultaneously, the description that simultaneously on employee performance. Emotional intelligence has a positive, organizational commitment has a positive and significant, organizational citizenship behavior has a positive and significant.Keywords: Emotional Intelligence, Organizational Commitment, Organizational Citizenship Behavior, and Employee Performance.